Risk factors and prevention of dabigatran‐related gastrointestinal bleeding in patients with atrial fibrillation - Nantsupawat, Teerapat (J Arrhythm, 2017)
INTRODUCTION: Dabigatran, as compared with warfarin, was associated with lower rates of stroke and systemic embolism with similar rates of major hemorrhage. But it has a significantly higher risk of gastrointestinal bleeding (GIB). There are limited data on how to prevent GIB from dabigatran and what are the risk factors. METHODS: We performed a retrospective cohort study of patients with atrial fibrillation who have ever taken dabigatran for thromboprophylaxis from October 2010 to February 2013. RESULTS: A total of 247 patients were identified. There were 10 (4%) patients who developed GIB (6 (6.5%) in PPI/H2RA users vs 4 (2.6%) in non‐PPI/H2RA users; P = .184). History of GIB within 1 year prior to dabigatran initiation and HAS‐BLED score ≥3 are independent risk factors for GIB, with odds ratio of 25.14 (95% CI, 2.85‐221.47; P < .01) and 5.85 (95% CI, 1.31‐26.15; P = .021), respectively. CONCLUSION: In this real‐world cohort, PPI/H2RA use was not associated with reduced GIB events. HAS‐BLED score ≥3 and prior history of GIB within 1 year are independent risk factors for GIB among dabigatran users.